A decision making tool for remanufacturing operations - Kafuku, John Mbogo (2017)
Remanufacturing industry is increasingly becoming one of the world's attractive business opportunities due to social, economic, and environmental benefits. However, high level of uncertainties in technology selection, imprecise information on availability of core quantity, and lack of standardization of parameters for holistic determination of cost and benefit in remanufacturing processes are among the challenges of this industry. This research developed a decision making tool that consists of a framework for technology selection, model for acquisition of core quantity, and cost and benefit analysis model. The framework considered eight parameters, which are technology costs, operating costs, disposal costs, technology functions, technology quality, technology flexibility, technology obsolete period, and disposal effects. The framework uses fuzzy logic for approximating information and uncertainties to produce results. The results showed that the technology obsolescence for a period of 5 years before it becomes outdated, with disposal effect of 80% leads to 90o/o environment effects. This justifies that rapid technology obsolescence has negative environmental effects. The research also developed a mathematical model to determine the optimal core quantity with the influence of an advertisement factor in controlling shortage of the core return. The model would help decision makers in envisaging availability of core for new remanufacturing investment; hence, a difficulty in core acquisition can be mitigated. The results indicated that the coefficient of media advertisement is a fundamental factor that influences increase rates of core quantity. The model shows that the advertisement factor can increase 41.50 of core availability, which is a step in reducing the degree of uncertainty for the acquisition of core. Moreover, tlte research developed cost and benefit analysis model using fuzzy logic to benchmark minimum cost based on parameters for the processes. The importance of the model is to determine specific values of parameters for the entire processes. The established parameters showed high risk to under-oroverestimate resources for an investment if they were treated in isolation from each process. The results of the case study showed that the increase of production quantity to 72.l2Yo has an advantage compared with the increase of product price to 59.84% as price increase will decrease profit by 44.80%. The framework is unique as it integrates obsolete and disposal phase to evaluate environmental issues. Besides, the mathematical model with advertisement factor has produced results to influence increase of core quantity and bridge the gap of uncertainty for core. Lastly, the cost and benefit model provided accurate value of a parameter to the entire operations, and helped the step-by-step procedures in determining cost and benefit considering standard parameters set to benchmark each process.